Evaluation of the transmission of SARS-CoV-2 through breast milk: a case series - Murano, Yayoi; Yamahira, Shinya; Shoji, Hiromichi; Hisata, Ken; Koshizaka, Takuya; Nakazawa, Tomoyuki; Shimizu, Toshiaki; Rahman, Mahbubur (Frontiers in Pediatrics, 2023)
Whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted through breast milk remains controversial. The purpose of this study is to determine the presence of SARS-CoV-2 in breast milk and assess its transmissibility to the child in infancy. Eleven samples were obtained from nine mothers with coronavirus disease 2019 (COVID-19). All but one sample had negative results on reverse transcription–quantitative polymerase chain reaction. Among nine children, five were diagnosed with COVID-19, including one child whose mother’s milk tested positive. Therefore, we concluded that although SARS-CoV-2 RNA can be detected in breast milk, the possible transmission via breastfeeding could not be established, might be present in breast milk, it seems unlikely that breast milk contributes to mother-to-child transmission or that and the physical attachment between mother and child is a conceivable transmission route.